It hurts, unless it s a hobby - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
A special survey conducted by Spore in Jamaica led to some revealing youth perspectives on farming as a future:'Before I went to college I was very motivated, wanted to graduate and do great things in agriculture, then I realised that it was dying....